Real estate investment funds and european private international law: notes on the judgement of the court of 3 October 2019, verein für konsumenteninformation, c-272/18 - Jiménez Palma, Eva (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The actuality and relevance of Case C-272/18 lies mainly on the fact that it is the first time that the Court of Justice has ruled on the treatment that the «real estate investment funds» must receive in the area of applicable law. In essence, it is analyzed whether these fiduciary structures are submitted within the material scope of the Rome I Regulation, distinguishing between contractual and corporate matters. In relation to the first one, it is examined whether are applicable the consumer protection rules inserted in that instrument, paying special attention to the exclusion provided for in its article 6.4.a) “services provided exclusively in a country other than that of the habitual residence of the consumer” and the choice of law regulated in its second section, in relation to Directive 93/13/EEC.